Generation of nitrile groups on graphites in a nitrogen RF-plasma discharge. (April 2015) - Mueller, Andreas; Schwab, Matthias Georg; Encinas, Noemi; Vollmer, Doris; Sachdev, Hermann; Müllen, Klaus
Abstract: Graphite particles were treated in a nitrogen radio frequency-plasma (RF-plasma) at different excitation power. The morphological as well as chemical surface modifications were investigated by Raman spectroscopy, SEM, and XPS. Changes of the sp 2 /sp 3 bonding ratio and selective surface terminations by functional groups were achieved. Especially, a direct functionalization of the graphites with nitrile groups was evidenced by a characteristic signal at 2240 cm −1 in the Raman spectra after a high energy RF-nitrogen plasma treatment. A total nitrogen content of up to 11 at.% was reached by the applied conditions. The increased polarity of the surfaces was confirmed by contact angle measurements. The nitrile functionalization may serve as synthetic scaffold for the development of new routes towards the chemical surface modification of carbon substrates. Furthermore, the modified graphites can be processed by common exfoliation techniques yielding nitrogen modified graphene nanoplatelets directly in polar and non-polar solvents.